2010
DOI: 10.1016/j.jmwh.2010.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Chain Omega‐3 Fatty Acids and Women's Mental Health in the Perinatal Period and Beyond

Abstract: Recent research has shown that depression and a range of physical illnesses, including heart disease, metabolic syndrome, and type 2 diabetes, have an inflammatory etiology. The long-chain omega-3 fatty acids (omega-3s) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which are found in fish and fish-oil products, may protect against these illnesses, in part because they lower inflammation. This article reviews the recent research on omega-3s and women's mental health, with a particular focus on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
12
0
3
Order By: Relevance
“…A study correlating DHA content in breast milk with postpartum depression revealed higher levels of depressive symptoms in women with low DHA levels when compared to women with higher levels 33 . A review of research, as presented in an article in this issue, 34 supports that n‐3 fatty acids lower levels of proinflammatory cytokines 2–4 . This characteristic helps n‐3s prevent and treat depression, cardiovascular disease, and other inflammatory conditions.…”
Section: Omega‐3 and Pregnancy Outcomesmentioning
confidence: 96%
“…A study correlating DHA content in breast milk with postpartum depression revealed higher levels of depressive symptoms in women with low DHA levels when compared to women with higher levels 33 . A review of research, as presented in an article in this issue, 34 supports that n‐3 fatty acids lower levels of proinflammatory cytokines 2–4 . This characteristic helps n‐3s prevent and treat depression, cardiovascular disease, and other inflammatory conditions.…”
Section: Omega‐3 and Pregnancy Outcomesmentioning
confidence: 96%
“…Jordan 55 stresses that pregnant women should consume between 200 and 300 mg of omega‐3 fatty acids daily from safe food sources, such as purified fish and algal oil supplements and docosahexaenoic acid (DHA)–enriched eggs, which are alternative sources for pregnant women who do not eat fish. Kendall‐Tackett 56 reviews recent research on omega‐3s and women's mental health, where the majority of studies indicate that eicosapentaenoic acid (EPA) has efficacy in treating depression, and that in moderate doses, EPA and DHA appear safe for pregnant and postpartum women. Kaludjerovic and Vieth 57 illustrate that inadequate vitamin D nutrition during perinatal development is a threat to human health and, because of the risks of exposure to sunlight, provides current recommendations for vitamin D supplementation 57 …”
Section: Diet and Pregnancymentioning
confidence: 99%
“…Fish is a good source of beneficial nutrients including high biological value protein, iodine, iron, selenium and vitamin E, 8 and is low in saturated fat. Evidence is emerging that low intakes of omega-3 fatty acids may contribute to the development of postnatal depression, 6,9,10 and increase the risk of pre-eclampsia 6,7,11 and gestational hypertension. 6 Optimal maternal omega-3 intake may lengthen gestation and increase birthweight.…”
Section: Introductionmentioning
confidence: 99%